Prediction by a Genetic Algorithm of the Fiber-Matrix Interface Damage for Composite Material. Part 2. Study of Shear Damage in Graphite/Epoxv Nanocomposites - Mokaddem, A.; Alami, M.; Ziani, N.; Bcldjoudi, N.; Boutaous, A. (Проблемы прочности, 2014)
The objective in this paper is to apply the same genetic model as applied in Part 1 to optimizing the shear damage to the fiber–matrix interface of nanocomposite material graphite epoxy. The results show good agreement between the numerical simulation and the actual behavior of the material chosen composite and nanocomposites, and these results are similar to results obtained by processing techniques expanded graphite reinforced polymer nanocomposites made by Asma Yasmine. These results were confirmed by calculating the rate of damage with a genetic simulation.